Understanding the Emergence of Entrepreneurial Passion: The Influence of Perceived Emotional Support and Competences - Pekka Stenholm; Mette Nielsen (Emerald, 2025)
Recent research acknowledges entrepreneurial passion’s outcomes, but far less is known about how entrepreneurial passion comes about. In this study, the authors are interested in the emergence of entrepreneurial passion, and how competences and social network are associated with entrepreneurial passion. The paper aims to discuss these issues. The authors investigate whether entrepreneurial passion emerges out of socialisation, entrepreneurial experience or various combinations thereof. The authors tested the hypotheses on a data set of entrepreneurs who started their businesses with government financial support (n=1150). The findings show that within a social environment, perceived emotional support is positively associated with entrepreneurial passion. Moreover, entrepreneurs’ task-related competence moderates this relationship positively. By investigating the emergence of entrepreneurial passion, the authors contribute to prior passion literature, which has mainly focused on its consequences.